PENGARUH BAURAN PEMASARAN JASA TERHADAP MINAT BELI ULANG CELEBRITY FITNESS METROPOLITAN MALL BEKASI - Jurgen Fernando; Agus Salim (Lembaga Penelitian dan Pengabdian kepada Masyarakat Institut Bisnis dan Informatika Kwik Kian Gie, 2019)
The growth of a fitness center currently in Jakarta and other major cities is growing rapidly, one of which is Celebrity Fitness. This was triggered by the growth of the middle class population and an increase in Indonesia's per capita income which signaled that the community had the opportunity to spend money on secondary needs, one of them exercising in a fitness center. The community will choose which fitness center is according to their desire to become a member. Celebrity Fitness is a fitness center that offers services for members to maintain their fitness and health. Celebrity Fitness feels the need to find out whether the services provided to its members have fulfilled their authority and whether they are consistent to remain as members. Research uses service marketing mix theory, which consists of products, prices, places, promotions, employees, physical evidence and processes to see their perceptions. If their perceptions are good about Celebrity Fitness services, of course they will consistently hold members or continue to do repeat purchases in the long term. The theory used in this study is the service marketing mix Â and repurchase intention. The analytical tool used is multiple regression analysis to analyze the service marketing mix relationship and the buying interest of Celebrity Fitness members. The conclusion of this study is that product variables, price, location, people, physical evidence and processes have a positive effect on repurchase intention variables, while promotion variables negatively affect repurchase intention variables.Keyword : Service marketing mix, repurchase intention, products, prices, places, promotions, employees, physical evidence, processes